SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN LOKASI PERUMAHAN MENGGUNAKAN METODE PROFILE MATCHING - Zulfan Efendi (STMIK Royal, 2019)
Abstract: In the business of property developers choosing a location to be an important decision for developers as a factor of attractiveness in housing marketing, if lack of observance in choosing the location of the location will result in slow sales, so that the company's profits become not optimal. For this reason, a decision support system is needed that can help developers in recommending housing locations that are in accordance with the wishes of the developer. The profile matching method is chosen because it can provide the closest value recommendation, so if there is no land the exact location in accordance with the wishes of the developer but the profile maching is able to provide the selection of the location with the closest profile value to the developer desired. Keywords: Decision support system, Developer, Property, Location Land, Profile matching. Abstrak: Lokasi merupakan faktor terpenting dalam usaha developer property, karena mempengaruhi tingkat pemasaran perumahan. Pemilihan lokasi menjadi keputusan penting, sehingga dibutuhkan suatu sistem pendukung keputusan yang tepat. Metode profile matching merupakan pilihan yang dapat memberikan rekomendasi. Hasil dari penelitian ini adalah memberikan rekomendasi dengan nilai terdekat, jadi walaupun tidak ada lahan lokasi yang sesuai persis keinginan developer tapi profile matching akan memberikan rekomendasi pemilihan lahan lokasi dengan profil yang terdekat sesuai harapan developer. Maka, dapat disimpulkan profile matching merupakan pilihan tepat dalam penentuan keputusan lokasi perumahan.